The e-Learning Quality Model to Examine Students’ Behavioral Intention to Use Online Learning Platform in a Higher Education Institution - Feby Artwodini Muqtadiroh; Anisah Herdiyanti; Noptrina Puspitasari (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2020)
This paper aims to understand the behavioral intentions of students in using e-learning in a public university in Indonesia. We apply the e-learning quality model to observe the quality factors that trigger intentions. The quality factors include assurance, empathy, responsiveness, reliability, and website content. Understanding how these quality learning factors may affect a student’s behavior intention to use e-learning is important to bring e-learning implementation success. We collected 502 responses from university students at a public university in Indonesia that implements a Moodle-based e-learning platform – namely ShareITS. Out of 5 (five) quality learning factors, we found only 2 (two) that significantly affect the e-learning quality – i.e., responsiveness and website content. The result shows that the teacher-student engagement in the e-learning platform and also the better visual design of ShareITS can improve the quality of the e-learning platform.